Historical Development of Reproductive Health in Sri Lanka - Seneviratne, H.R. (Faculty of Medicine, University of Colombo, 2020)
The Components of Reproductive Health (RH) were in place from ancient times and later evolved to what it is today. Initially the local inputs were the driving force, it changed direction during the colonial times. The establishment of this prestigious institution 150 years ago was such an event. Today the policies and practices of RH are directed and funded by the wishes of International agencies. National developments by the FOM are the WHO collaborated Reproductive Health Research in Sri Lanka (1979, 1999)), initiation of Maternal Medicine (1979) and introduction of Advanced Fertility Treatment (1996). It is hoped that the FOM would harness its expertise and resources effectively for further development of RH in the country.
Keywords: Reproductive Health; Sri Lanka